Alcoholism and violence in the family - Yilán Lobo-Rodríguez; Mirian Rodríguez-Bejerano; Katherine Vidal-Rodríguez (Universidad de Guantánamo, 2012)
This work was accomplished in the community "28 de September" where the basic secondary school "Daniel Llosas Preval" is located. The research was carried out with the families of 38 students with special educative needs. These students constitute a group which has been granted great priority since they have cognitive, communicative and prophylactic needs. An extensive work was carried out by the school staff and the different factors with the aim of identifying relevant aspects concerning alcoholism and some facets of violence in the family, to assess each pupil with difficulties, as well as applying a system of actions that contribute to improve the prophylactic work in the community. We used various methods and techniques of scientific investigation and Popular Education, they allowed us to gain knowledge and reflect on the issue, of great importance for the formation of the personality of the new generations.